If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(p + 9) + -12p = 51 Reorder the terms: 3(9 + p) + -12p = 51 (9 * 3 + p * 3) + -12p = 51 (27 + 3p) + -12p = 51 Combine like terms: 3p + -12p = -9p 27 + -9p = 51 Solving 27 + -9p = 51 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + -9p = 51 + -27 Combine like terms: 27 + -27 = 0 0 + -9p = 51 + -27 -9p = 51 + -27 Combine like terms: 51 + -27 = 24 -9p = 24 Divide each side by '-9'. p = -2.666666667 Simplifying p = -2.666666667
| 6-6x+3x=-21 | | 11p=22 | | 5x+10+11x+2+58=360 | | 4x^2+5x=-12 | | 12(m+20)=16m | | x(2)+5x-14=0 | | 8w-30=5w-40 | | 4x^2=-12x-6 | | (x/4)=(x/5)+(7/4) | | 2y-1/21=3y-7/15 | | 10+x+60=90 | | 10=2(2x-1) | | -0.08y+0.10(800-y)=0.07y | | 3x/x+2-x/x-2+8/x^2-4 | | 3x=x+10+2 | | 1/2x-3=-2 | | 4+10m-5+2m=1 | | 3x/x+2-x/x-2+8/x2-4 | | 3/5x-1=5 | | n(2)=-8n-7 | | 2/7x+8=0 | | 2n^2+6n=108 | | -7x-6=-6 | | 3(x-3)+6=-4+x-23 | | 15-1/5x=5 | | 2(2x+2)=12 | | -6x-6=-6 | | 8-1/4x=-4 | | -8y+18=5y-6 | | x(2)-48=-2x | | x-17=-11 | | 2c-3d=6 |